PENGARUH PEMUPUKAN NPK DAN MONO KALIUM PHOSPAT TERHADAP HASIL TANAMAN KACANG MERAH (Phaseolus vulgaris L.) ASAL TUAL MALUKU TENGGARA - Dominggus Marcus Donald Tatuhey; Herman Masbaitubun; Paskalius Apriyanto Merahabia; Lispin Yanus Wanimbo (Jurnal Pertanian Terpadu Santo Thomas Aquinas, 2026)
Red kidney bean (Phaseolus vulgaris L.) is one of the food crops that requires both macro and micro nutrients to support growth and production. The availability of these nutrients can be fulfilled through the application of appropriate and balanced fertilizers. NPK and MKP fertilizers are inorganic fertilizers that supply nitrogen (N), phosphorus (P), and potassium (K). This study aimed to determine the effect of NPK and MKP fertilization on the production of red kidney bean plants. The method used was an experimental approach. The results showed that: (1) the application of NPK and MKP fertilizers had no significant effect on growth variables, but had significant and highly significant effects on yield variables; (2) the P3 fertilization dose (NPK 200 kg/ha and MKP 150 kg/ha) produced the highest number of pods, pod length, and pod dry weight.